2D and 3D imaging of the deformation behavior of partially devulcanized rubber/polypropylene blends - P. S. Garcia; R. F. Gouveia; J. M. Maia; C. H. Scuracchio; S. A. Cruz (eXPRESS Polymer Letters, 2018)
The full understanding of the mechanisms involved in the development of polymer blend microstructure during its processing has not yet been achieved; the understanding of blends composed by a highly elastic dispersed phase is even more indefinite. The proposal of this work is to analyze the deformation behavior of a new system composed by a partially devulcanized rubber dispersed in polypropylene using 2D and 3D images, both as complementary tools. For this purpose, ground tire rubber (GTR) was partially devulcanized by microwave irradiation for different exposure periods. After this step, each treated rubber was incorporated into recycled PP. The molded blends were analyzed using effective tools as 2D and 3D images and rheological data. In general, the polymer blends exhibited refined microstructure, especially the blend composed of the most devulcanized rubber, even though they had high values of viscosity ratio (≥4). Based on the 3D images, it is clear that breakup mechanisms of the dispersed phase, like parallel breakup, have played an important role in the evolution of the blend’s microstructure, mainly in the region of higher shear rate during processing. However, in areas where the rubber is still vulcanized, the breakup may have been caused by erosion of its surface.